Effective Onboarding and Socialization Tactics: A Communication Psychology Approach to Human Resource Management - Paulus, P. (Manunggal Halim Jaya, 2023)
In the dynamic landscape of contemporary human resource management, effective onboarding and socialization processes emerge as crucial elements for organizations striving to cultivate a productive and engaged workforce. This exploration delves into the intricate interplay between organizational communication and human psychology to unravel the dynamics that contribute to successful onboarding. By adopting a communication psychology approach, this discourse aims to provide a comprehensive understanding of how tailored communication strategies can enhance the onboarding experience, foster employee satisfaction, and contribute to organizational success.